2017
DOI: 10.17221/5/2017-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Growth, carcass, and physiological traits of growing male China Micro-ducks fed various levels of dietary crude fibre

Abstract: The objective of this study was to evaluate the responses of growth performance, organ development, carcass characteristics, and serum biochemical parameters to the diets with different levels of crude fibre (CF) in growing male China Micro-ducks (CMD). A total of 240 nineteen-day-old CMD were blocked on the basis of body weight, and then randomly allocated to four treatments, each with 6 replicate pens of 10 ducklings. The formal feeding experiment lasted for 35 days. The CF levels for four diets were 16.7, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
(32 reference statements)
2
11
0
Order By: Relevance
“…Yang (2002) asserted that alfalfa can be fed to waterfowl because the CF derived from alfalfa is largely digestible. According to production practice, it has been observed that CMD adapts well to various fibrous feedstuffs (Wang et al, 2013;Wang et al, 2017). The present results revealed that dietary fibre levels also altered the ratios of some constituents existing in the breast muscle of growing CMD.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Yang (2002) asserted that alfalfa can be fed to waterfowl because the CF derived from alfalfa is largely digestible. According to production practice, it has been observed that CMD adapts well to various fibrous feedstuffs (Wang et al, 2013;Wang et al, 2017). The present results revealed that dietary fibre levels also altered the ratios of some constituents existing in the breast muscle of growing CMD.…”
Section: Discussionsupporting
confidence: 56%
“…The experimental design and procedures were approved by the Animal Care and Use Committee of Southwest University following the requirements of the Regulations for the Administration of Affairs Concerning Experimental Animals of China (The State Science and Technology Commission, 1988). The bird husbandry and the experimental design have been described in detail by Wang et al (2017). The experimental diets (Table 1) were formulated to meet or exceed the NRC (1994) recommendations for growing ducks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the experiment, the birds were weighed and feed consumption was recorded to calculate average daily gain (ADG), average daily feed intake based on dry matter (DM) and FCR (feed DM intake/weight gain). The birds were deprived of feed for 12 hours (water was provided) before weighing to ensure that the digestive tracts of the birds (Wang et al, 2017) were emptied. Mortality was recorded daily as it occurred.…”
Section: Methodsmentioning
confidence: 99%
“…The dressed percentage was calculated by dividing the dressing weight by the slaughter weight. The half-eviscerated weight was evaluated as the weight of carcass without trachea, oesophagus, pseudo-crop, guts, spleen, pancreas, gall bladder, reproduction organs and the chime and gizzard (Wang et al, 2017). The eviscerated weight was quantified when the weights of heart, liver, proventriculus, gizzard, lungs and abdominal fat were subtracted from the half-eviscerated weight.…”
Section: Methodsmentioning
confidence: 99%